Providing efficient user management for large-scale enterprise by achieving high scalability over cloud. (2017) - Priya, G. Nalini; Sangaiah, Arun Kumar; Thangavelu, Aishwarya; Murali, Thusitha; Balusamy, Balamurugan
Cloud computing is an emerging computing technology, almost used by all the big enterprises to store and access their private organisational data. It also helps to manage the complex work and to process in easy and secure manner. Access control models provide authorisation and authentication to the users in pursuance of providing security over the data in the cloud. Big enterprises prefer role-based access control (RBAC) model to manage the different roles in the management. A drastic problem called 'role explosion' occurs in RBAC due to the random increase in the number of users and roles in an organisation. In this paper, we propose a variant data structure model for the role-based access control model namely scalable bloom filter-role-based access control (SBF-RBAC) model. Our proposed model implements scalable bloom filters for each role so that there could be a dynamic accommodation of users in the roles that reduce space complexity.